2019
DOI: 10.33224/rrch/2019.64.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using a mountain plant extract

Abstract: The present study investigated the synthesis of silver nanoparticles (Ag-NPs) using Artemisia Sieberi Besser leaf extract. To evaluate parameters affecting the synthesis including pH, volume of extract, concentration of silver nitrate solution, temperature and time, Ultraviolet-Visible (UV-Vis) spectroscopy was used. Ag-NPs were characterized by UV-Vis spectroscopy, Scanning electron microscopy (SEM), X-ray diffraction spectroscopy (XRD), Fourier transform infrared spectroscopy (FTIR) and Transmission Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The phytochemical analysis of A. sieberi revealed that it was rich in amines, carboxylic groups (such as alcohols and phenols), and alkenes. In agreement with these findings, a previous study showed that the FTIR analysis of the leaf extract of A. sieberi had the highest peaks for hydroxyl groups, alkanes, alkenes, amides, and amines [23,24]. In addition, the study conducted by Alotibi and Rizwana (2019) revealed that the methanolic extract of A. sieberi was rich in the functional groups of OH, CH stretching, C=O stretching, and aromatic skeletal stretches, which agreed with the current results as well [25].…”
Section: Discussionsupporting
confidence: 85%
“…The phytochemical analysis of A. sieberi revealed that it was rich in amines, carboxylic groups (such as alcohols and phenols), and alkenes. In agreement with these findings, a previous study showed that the FTIR analysis of the leaf extract of A. sieberi had the highest peaks for hydroxyl groups, alkanes, alkenes, amides, and amines [23,24]. In addition, the study conducted by Alotibi and Rizwana (2019) revealed that the methanolic extract of A. sieberi was rich in the functional groups of OH, CH stretching, C=O stretching, and aromatic skeletal stretches, which agreed with the current results as well [25].…”
Section: Discussionsupporting
confidence: 85%
“…The pH of the reaction changes the chemical nature of the extract, which has an effect of changing its performance and rate of reduction and therefore nanoparticle synthesis [36]. The size and shape of silver nanoparticles are affected by the pH of the reaction solution [37][38][39][40]. This was investigated further with the addition of hydrochloric acid (HCl), which did not produce any nanoparticles (Figure 2).…”
Section: Uv-vis Spectra Analysismentioning
confidence: 99%
“…Then, the yielded aqueous extract was filtered by whatman filter paper (grade 42-UK, with pore size 20 μ). After that, the sample was placed in the centrifuge (Superspeed Sorvall B-RC2) at the speed of 9000 rpm for 10 min [30]. Finally, the aqueous extract was put in the refrigerator at 4 °C.…”
Section: Physical Methods Includingmentioning
confidence: 99%